Neural Correlates of Spatial Navigation Changes in Mild Cognitive Impairment and Alzheimer’s Disease - Vlček, Kamil; Laczó, Jan (Frontiers in Behavioral Neuroscience, 2014)
Although the memory impairment is a hallmark of Alzheimer’s disease (AD), AD has also been characterized by spatial disorientation, which is present from its early stages. Spatial disorientation in AD manifests itself in getting lost in familiar and unfamiliar places and have been characterized more specifically using spatial navigation tests in both real space and virtual environments as an impairment in multiple spatial abilities, including allocentric and egocentric navigation strategies, visuospatial perception or selection of relevant information for successful navigation. Patients suffering mild cognitive impairment (MCI), who are at a high risk of development of dementia, show impairment in a subset of these abilities, mainly connected with allocentric and egocentric processing. While spatial disorientation in typical AD patients probably reflects neurodegenerative changes in medial and posterior temporal, parietal and frontal lobes and retrosplenial cortex, the impairment of spatial navigation in MCI seem to be connected mainly with the medial temporal and also parietal brain changes. In this review we will summarize the signs of brain disease in most MCI and AD patients showing in various tasks of spatial memory and navigation.